2021
DOI: 10.1186/s12864-021-07764-2
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene screening for lipid deposition using combined transcriptomic and proteomic data from Nanyang black pigs

Abstract: Background Lower selection intensities in indigenous breeds of Chinese pig have resulted in obvious genetic and phenotypic divergence. One such breed, the Nanyang black pig, is renowned for its high lipid deposition and high genetic divergence, making it an ideal model in which to investigate lipid position trait mechanisms in pigs. An understanding of lipid deposition in pigs might improve pig meat traits in future breeding and promote the selection progress of pigs through modern molecular br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…It has been shown that in animal organisms, the ACACA gene is highly expressed in tissues with strong fatty acid metabolic activity, and the acetyl coenzyme A carboxylase (ACACA) gene plays an important role in lipid metabolism by promoting fatty acid biosynthesis ( 26 ). The results of our study also showed extremely high expression in porcine dorsal lipid tissues, which is consistent with the findings of previous studies ( 27 , 28 ). Solute carrier family 2 member 4 (SLC2A4), also known as glucose transporter protein 4 (GLUT4), is an important transporter protein for cellular uptake of glucose, mainly expressed in muscle and adipose tissues, involved in active cellular uptake of glucose across membranes, and plays an important role in glucose metabolism, and was enriched in the present assay in AMPK signaling pathway, insulin signaling pathway and adipocyte factor signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that in animal organisms, the ACACA gene is highly expressed in tissues with strong fatty acid metabolic activity, and the acetyl coenzyme A carboxylase (ACACA) gene plays an important role in lipid metabolism by promoting fatty acid biosynthesis ( 26 ). The results of our study also showed extremely high expression in porcine dorsal lipid tissues, which is consistent with the findings of previous studies ( 27 , 28 ). Solute carrier family 2 member 4 (SLC2A4), also known as glucose transporter protein 4 (GLUT4), is an important transporter protein for cellular uptake of glucose, mainly expressed in muscle and adipose tissues, involved in active cellular uptake of glucose across membranes, and plays an important role in glucose metabolism, and was enriched in the present assay in AMPK signaling pathway, insulin signaling pathway and adipocyte factor signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with western pig breeds, Chinese indigenous pigs have a slow growth rate and low lean meat rate but have excellent meat quality and superior lipid deposition. The population of Chinese indigenous pig breeds is small, the breeding method is relatively closed, and the selection intensity is low, resulting in obvious genetic and phenotypic differentiation [ 7 ]. The Wannanhua (WH) pig is an excellent indigenous pig breed from Anhui Province.…”
Section: Introductionmentioning
confidence: 99%
“… Zhang et al (2022a) considered FASN a candidate gene for fat deposition. Another study showed a strong correlation between FASN and intramuscular fat ( Wang et al, 2020 ), and FASN determined lipid deposition using transcriptome and proteome data ( Wang et al, 2021 ). The mRNA expression of FASN in the subcutaneous fat was higher than that in the perirenal fat.…”
Section: Discussionmentioning
confidence: 99%